Institutional constraints to the integration of food and nutrition security in district planning: A case study from Nampula Province, Mozambique (Research, Society and Development, 2026)
The objective of this study is to investigate institutional, methodological, and capacity-related factors that hinder the effective integration of Food and Nutritional Security (FNS) into the District Strategic Development Plans in Mozambique. A mixed-methods research is conducted focusing on a case study involving social research through interviews and document analysis in a qualitative investigation. This article explores the challenges involved in integrating FNS into District Strategic Development Plans (PEDDs) in Mozambique. Drawing from a case study in the Nampula Province, the study investigates the effectiveness of government-led efforts to mainstream cross-cutting issues particularly FNS into decentralized development planning. Guided by Parsons’ theory of evolutionary social change, the research applies a qualitative methodology combining document analysis and 45 semi-structured interviews with district and provincial planning teams. The findings reveal that the limited participation of central institutions like the Ministry of Planning and Development, the lack of clear integration indicators, poor harmonization of methodologies, and weak technical knowledge among planning teams are critical obstacles. These insights are relevant for improving multi-sectoral planning strategies aimed at addressing persistent food insecurity and malnutrition in rural areas of Mozambique.